Influenza Viral Shedding in a Prospective Cohort of HIV-Infected and Uninfected Children and Adults in 2 Provinces of South Africa, 2012–2014. (24th May 2018) - von Mollendorf, Claire; Hellferscee, Orienka; Valley-Omar, Ziyaad; Treurnicht, Florette K; Walaza, Sibongile; Martinson, Neil A; Lebina, Limakatso; Mothlaoleng, Katlego; Mahlase, Gethwana; Variava, Ebrahim; Cohen, Adam L; Venter, Marietjie; et al.
Abstract : In the era of an established antiretroviral treatment program, no difference was detected in influenza virus shedding in HIV-infected and -uninfected individuals recruited from outpatient clinics. However, HIV-infected individuals with lower CD4 counts shed for longer than less-immunocompromised individuals. Abstract: Background: Prolonged shedding of influenza viruses may be associated with increased transmissibility and resistance mutation acquisition due to therapy. We compared duration and magnitude of influenza shedding between human immunodeficiency virus (HIV)-infected and -uninfected individuals. Methods: A prospective cohort study during 3 influenza seasons enrolled patients with influenza-like illness and a positive influenza rapid test. Influenza viruses were detected by real-time reverse transcription polymerase chain reaction. Weibull accelerated failure time regression models were used to describe influenza virus shedding. Mann-Whitney U tests explored initial influenza viral loads (VL). Results: Influenza virus shedding duration was similar in 65 HIV-infected (6 days; interquartile range [IQR] 3–10) and 176 HIV-uninfected individuals (7 days; IQR 4–11; P = .97), as was initial influenza VL (HIV-uninfected 5.28 ± 1.33 log10 copies/mL, HIV-infected 4.73 ± 1.68 log10 copies/mL; P = .08). Adjusted for age, HIV-infected individuals with low CD4 counts shed influenza virus for longer than those with higher counts (adjusted hazard ratio 3.55; 95% confidence interval, 1.05–12.08). Discussion: A longer duration of influenza virus shedding in HIV-infected individuals with low CD4 counts may suggest a possible increased risk for transmission or viral evolution in severely immunocompromised individuals. HIV-infected individuals should be prioritized for annual influenza immunization.